Multidisciplinary Team Managements and Clinical Outcomes in Patients With Pulmonary Arterial Hypertension During the Perinatal Period - Shu, Tingting; Feng, Panpan; Liu, Xiaozhu; Wen, Li; Chen, Huaqiao; Chen, Yunwei; Huang, Wei (Frontiers in Cardiovascular Medicine, 2021)
Background: Pulmonary arterial hypertension (PAH) patients with pregnancy have high maternal mortality. This study aimed to provide clinical evidence with multidisciplinary team (MDT) management and to evaluate the clinical outcomes in PAH patients during the perinatal period. Methods: We conducted a retrospective evaluation of PAH patients pregnant at the First Affiliated Hospital of Chongqing Medical University between May 2015 and May 2021. Results: Twenty-two patients (24 pregnancies) were included in this study and received MDT management, and 21 pregnancies chose to continue pregnancy with cesarean section. Nine (37.5%) were first-time pregnancies at 27.78 ± 6.16 years old, and 15 (62.5%) were multiple pregnancies at 30.73 ± 3.71 years old. The average gestational week at hospitalization and delivery were 29.38 ± 8.63 weeks and 32.37 ± 7.20 weeks, individually. Twenty-one (87.5%) pregnancies received single or combined pulmonary vasodilators. The maternal survival rate of PAH patients reached 91.7%. Fifteen (62.5%) pregnancies were complicated with severe adverse events. Patients with complicated adverse events showed lower percutaneous oxygen saturation (SpO2), lower albumin, lower fibrinogen, higher pulmonary artery systolic pressure (PASP), higher blood pressure, longer activated partial thromboplastin time, and longer coagulation time. Fourteen (66.7%) pregnancies with cesarean sections were prematurely delivered and 85.7% newborns who survived after the operation remained alive. Conclusion: The survival rate of parturients with PAH was improved in relation to MDT and pulmonary vasodilator therapy during the perinatal period compared with previous studies. SpO2, albumin, PASP, blood pressure, and coagulation function should be monitored carefully in PAH patients during pregnancy.